Brushite: a Reclaimed Phosphorus Fertilizer for Agricultural Nutrient Fertilization - Harrison R. Coker; Rui Yang; Isaiah J. Robertson; Joshua M. Doria; Katie L. Lewis; Julie A. Howe (Journal of Soil Science and Plant Nutrition, 2025)
Phosphorus fertilizers are typically produced from mined and chemically processed rock phosphate, which is a diminishing non-renewable resource. Wastewater-reclaimed phosphorus minerals, such as brushite (CaHPO 4 ·2H 2 O), have the potential to be utilized as agricultural fertilizers. The commercial recovery of brushite from wastewater processing is a recent advancement; however, its efficacy as an agricultural fertilizer has yet to be evaluated. Wastewater-reclaimed brushite was tested in a greenhouse and field setting. In the greenhouse study, two P-limited soils were used to grow corn fertilized using brushite and were compared with struvite (NH 4 MgPO 4 ·6H 2 O), another reclaimed P source, and conventional P fertilizers, triple super phosphate (TSP) and monoammonium phosphate (MAP). In the field, corn, wheat, and cotton were grown in two ecoregions for two sites years to compare brushite and struvite with conventional fertilizers. Plants were evaluated for P uptake and yield, and P availability was determined as extractable P. Results indicate that brushite promoted plant productivity similar to conventional fertilizers in P-limited greenhouse soils. Field studies demonstrated similar uptake and assimilation of brushite-P compared to synthetic fertilizers and struvite. Soil acidification occurred across all fertilization treatments. The use of reclaimed brushite as a P fertilizer appears to be as effective as commercially available synthetic fertilizers.